2018
DOI: 10.1103/physreva.98.013840
|View full text |Cite
|
Sign up to set email alerts
|

Exchange of optical vortices using an electromagnetically-induced-transparency–based four-wave-mixing setup

Abstract: We propose a scheme to exchange optical vortices of slow light using the phenomenon of electromagnetically induced transparency (EIT) in a four-level double-Λ atom-light coupling scheme illuminated by a pair of probe fields as well as two control fields of larger intensity. We study the light-matter interaction under the situation where one control field carries an optical vortex, and another control field has no vortex. We show that the orbital angular momentum (OAM) of the vortex control beam can be transfer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 67 publications
0
40
0
Order By: Relevance
“…It has been recently shown that a double-Λ scheme can be employed for the exchange of optical vortices based on EIT [55]. In the double-Λ scheme there should be two additional control lasers of larger intensity to assure the exchange of optical vortices.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently shown that a double-Λ scheme can be employed for the exchange of optical vortices based on EIT [55]. In the double-Λ scheme there should be two additional control lasers of larger intensity to assure the exchange of optical vortices.…”
Section: Discussionmentioning
confidence: 99%
“…where γ R = γ L = γ. The parameter L is the length of the atomic medium and α defines the optical depth for both right and left fields [30]. Substituting Eq.…”
Section: Closed-loop Three-level V -Type Atomic Systemsmentioning
confidence: 99%
“…Now, we are going to find the amplitude of the GFF using the Maxwell equations. In the slowly varying envelope approximation and assumption of time-independent probe fields the Maxwell equations for two weak probe fields, propagating in z direction, read towhere α and L are the optical depth of the probe fields and atomic vapor cell length, respectively 22 . Considering the initial conditions for the probe fields amplitudes at the atomic medium entrance as Ω 41 ( z = 0) = 0 and Ω 21 ( z = 0) = Ω 21 (0), and δ = 0, simultaneous solving of equations (3) and (4) leads to an explicit term for the Rabi frequency of the GFF asin whichandat z = 0.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Generation of the optical vortex beams from a non-vortex beam occurred by a wave mixing process in a nonlinear photonic crystal 15 . Several nonlinear optical processes have been studied in different quantum systems using LG beams 16 such as the second-harmonic generation 9,17 , sum frequency generation 18 , and four-wave mixing (FWM) 1922 . The spatially structured optical transparency is theoretically investigated in a five-level combined tripod and Λ atom-light coupling scheme 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation